Enzymatic processing and MHC loading 1Pre-mRNA derived antigenic peptides for the MHC class I pathway are generated in the nucleus. (October 2022) - Fahraeus, Robin; Prado-Martins, Rodrigo; Daskalogianni, Chrysoula; Sroka, Ewa; Labedz, Agata; Apcher, Sebastien
Abstract : Mass spectrometry data show that peptides derived from alternative sources and from alternative processing are presented on MHC class I molecules. We have focused on pre-mRNAs as a source and we have show that peptides from pre-spliced mRNAs are presented directly, cross-presented and expressed in animals. The pioneer translation event producing these peptide substrates is distinct from the canonical translation that generates full length proteins. This can help to explain how the regulation of protein synthesis does not affect antigen presentation. It also offers an explanation to how tolerance is generated against alternative tissue-specific splicing products. The pioneer translation is a target for viral immune evasion and we can show it forms an opportunity for new therapeutic intervention. Even though an alternative translation event producing antigenic peptide substrates helps to answer some questions, it also raises some others to which one needs to consider unorthodox possibilities, such as nuclear translation. This is a wonderfully controversial possibility, but nevertheless, quite plausible. But alternative sources of translation products for the class I pathway also raises some questions for which not even nuclear translation can offer an explanation and it is inspiring to think that one might need to dig further and consider new cell biological concepts to provide the answers.